A selecting of a suitable CHARTIS EUROPE S.A. product by using multi criteria decision making - Jirousková, Nikola (2012)
This thesis addresses the question of whether it is good to insure as a young man who pays very small amount or interest to the insurance when a person goes into retirement and when the injury heals worse and longer. The target of this thesis is to determine which insurance product from CHARTIS EUROPE S.A. is advantageous for young and for old person. I solve this issue in the practical part of this thesis by using multi-criteria decision making.